1994
DOI: 10.7164/antibiotics.47.792
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activities of indolocarbazole and bis-indole protein kinase C inhibitors.

Abstract: The antimicrobial activities of twenty-twosubstances structurally related to staurosporine, aglycone in the indolocarbazole and bis-indole series were examined against Streptomyces chartreusis and Streptomyces griseus, Bacillus cereus, Escherichia coli, Candida albicans and Botrytis cinerea. Inhibition of sporulation was examined also on the two species of Streptomyces. Unlike literature reports for efficient protein kinase inhibitors, staurosporine and K-252a, no evident correlation could be found either betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 18 publications
1
22
0
1
Order By: Relevance
“…Studies have shown that some indolocarbazole compounds, such as rebeccamycin, inhibited the growth of streptomycete strains, whereas other indolocarbazole compounds, such as staurosporine, allowed growth but affected cell differentiation in the tested strains (36,37). Therefore, a possibility existed at the beginning of this study that some of the generated derivatives could affect the growth of the host, S. albus.…”
Section: Discussionmentioning
confidence: 95%
“…Studies have shown that some indolocarbazole compounds, such as rebeccamycin, inhibited the growth of streptomycete strains, whereas other indolocarbazole compounds, such as staurosporine, allowed growth but affected cell differentiation in the tested strains (36,37). Therefore, a possibility existed at the beginning of this study that some of the generated derivatives could affect the growth of the host, S. albus.…”
Section: Discussionmentioning
confidence: 95%
“…Halogenation is an important feature for the biological activity of a large number of different natural products. [39][40][41] The interest in and knowledge of halogenating enzymes is increasing rapidly. There are two subtypes of halogenases that are known to be involved in the biosynthesis of secondary metabolites: the FADH 2 -dependent halogenases that act upon aromatic or heteroaromatic rings, which is the subtype that was used in this study, and the recently discovered non-heme Fe II halogenases, which act on aliphatic groups.…”
Section: A C H T U N G T R E N N U N G Expression Host (mentioning
confidence: 99%
“…In many cases, the number, type and position of halogen groups in organic compounds are important for biological activity (see Nogami et al, 1990;Otsuka et al, 2004;Sancelme et al, 1994). Concerning cyanopeptolins, both chlorinated and non-chlorinated peptides have been described, e.g.…”
Section: Halogenases and Halogenated Cyanopeptolinsmentioning
confidence: 99%